2015
DOI: 10.5935/0104-7795.20150017
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy in sexually dysfunctional women: a systematic review

Abstract: The World Health Organization (WHO) considers Female Sexual Dysfunctions (FSDs) to be a public health issue. There are a multitude of disorders such as female sexual arousal disorder, hypoactive sexual desire disorder, orgasmic disorder, dyspareunia, and vaginismus. FSDs are detected in 67.9% of the women in the world and are present in 50% of Asians, in 30-50% of Americans, and in 30% of Brazilians. Objective: To systematically review the literature on the different physiotherapy techniques used in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(39 reference statements)
0
1
0
4
Order By: Relevance
“…In the results of the Aslan study, Aslan et al [19] showed success in the treatment of vaginismus with electrostimulation (FES) used in analgesic frequency, producing a defensive reflex as a mechanism against nociception [26]. In this way, tolerance to touch was potentiated and, subsequently, there was an improvement in sexual function allowing for a satisfactory sexual relationship [27]. However, the relaxation techniques of PFM and massage must be associated, as the mobilization of tissues causes heat and helps in the organization of collagen and reduction of adhesions and can relieve local pain [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the results of the Aslan study, Aslan et al [19] showed success in the treatment of vaginismus with electrostimulation (FES) used in analgesic frequency, producing a defensive reflex as a mechanism against nociception [26]. In this way, tolerance to touch was potentiated and, subsequently, there was an improvement in sexual function allowing for a satisfactory sexual relationship [27]. However, the relaxation techniques of PFM and massage must be associated, as the mobilization of tissues causes heat and helps in the organization of collagen and reduction of adhesions and can relieve local pain [28].…”
Section: Discussionmentioning
confidence: 99%
“…Após a intervenção fisioterapêutica, o GAM obteve melhora estatisticamente significante, diferentemente do GDE, provavelmente pelo uso adequado do dilatador vaginal e da massagem perineal, feitos pelo profissional. Estas técnicas contribuem para reversão da dispareunia [20,23].…”
Section: Discussionunclassified
“…Contudo, o TMAP aumentou o tônus, o recrutamento das fibras e a vascularização pélvica, levando a melhora da função muscular. A massagem perineal possibilitou redução da hipertonia muscular [20,23,26]. Com este protocolo, houve melhora significativa quanto à endurance, a potência e o grau de força desses músculos, nas participantes do GAM e, no GDE, observou-se mudança estatisticamente significante apenas no que se refere as variáveis de grau de força e endurance.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Como forma de tratamento para a SBH, a Sociedade Internacional de Continência recomenda o método conservador, incluindo Fisioterapia e Terapia Comportamental [18]. O TMAP permite a contração e relaxamento voluntário da musculatura pélvica, estudos afirmam que esse aumenta o tônus e o recrutamento muscular local com consequente incremento da vascularização pélvica, além da conscientização e propriocepção da musculatura da região perineal e, associados com a realização da MP promovem melhora da contratilidade [19][20][21].…”
Section: Methodsunclassified